Advanced directives of will: legal and educational challenges in the nurse's view - Isabela Saioron; Flávia Regina Souza Ramos; Felipa Rafaela Amadigi; Paola da Silva Diaz (Universidade Federal de Goias, 2017)
The Advanced directives of will (ADW) are documental registries which the individual describes the procedures that he or she would like to be submitted or not. The objective of this article is to discuss the emerging challenges to use the ADW in ethical-legal and educational terms from the nurse's view. An exploratory qualitative study composed of semi-structured interviews with 19 nurses from the Intensive Care and Medical Clinic of a University Hospital. We conducted the data analysis folling the Discursive Textual Analyisis technique. Two main categories of challenges associated to ADW emerged: Legal challenges related to ADW adoption in Brazil and Educational and knowledge challenges related to ADW adoption; besides other results also reported here. The taboo related to death, the lack of legal backing and professional training related to terminality and autonomy of the patient, arise as challenges to promote and to use ADW in the studied reality.